New Horizons for Innovation Policy and Evaluation - Kuusisto, Jari; Flowers, Stephen (De Gruyter, 2024)
The chapter draws together implications of the work and looks ahead to the future of innovation policy and evaluation. We recognise the profound changes in the realm of innovation, and the shift from traditional, narrow approaches to a more inclusive and dynamically complex perspective. This transformation is influenced by a broader understanding of innovation, the impacts of crisis, climate change, and the evolution of societal structures. It highlights how outdated assumptions about innovation are being challenged by realities that include diverse contributors beyond just firms and traditional markets. Innovation is increasingly understood as embedded in the complexity of modern societal structures, characterized by deep interconnectivities. This creates a need for new policy evaluation frameworks and concepts. The ones that are flexible, dynamic, capable of addressing the multifaceted impacts of innovation across economic, environmental, and social domains. These frameworks must also account for the intersectionality present in modern societal issues, which are interwoven rather than discrete as well as the exponential, rather than linear, effects of innovation. Such approach reflects a shift from promoting technological advancement in isolation to fostering a broader range of innovations that include services, environmental sustainability, and social inclusivity. Finally, evaluations should not only seek to measure economic impacts but also how well policies promote inclusivity, environmental sustainability, and social equity.